Performance Assessment of Multi-story Building After 24 Years in Service - Saidi*, Taufiq; Muttaqin*, Muttaqin; Muzhaffar, Imam; Setiawan, Bambang; Juellyan, Juellyan (Aceh International Journal of Science and Technology, 2023)
Any public infrastructure has a set service life limit. In the Indonesian case, the public building has a 50-year design life. This paper presents a performance assessment of a multiple-story building in Aceh-Indonesia. A multi-story Faculty of Engineering Universitas Syiah Kuala building was used in this study. This multi-story building structure has been used for more than 24 years since it was built in 1998. This structure is 29.4 m long, 13 m wide, and 14.4 m tall in geometric terms. This study reveals how this three-story building behaves, including displacement, base shear, and structure performance level per ASCE 41-17 criteria. The processes in this study are broken down into various stages, including pushover analysis and comparing the building's current natural frequency. ETABS software was used to model building structures. According to the study, the building's performance is still more or less similar to the initial plan. Pushover in the X-direction (Push X) is believed to be immediate occupancy (IO), and pushover in the Y-direction (Push Y) is believed to be life safety (LS). The pushover analysis results for Push X suggested that the structure is safe and retains rigidity. Push Y indicated minor damage within the life safety category after a service life of 24 years. This pushover analysis indicated that the structure has reduced its rigidity, making it less able to resist further displacement. Based on the base shear, which experiences a displacement that is significantly greater than the estimate at the original planning stage, it is known that stiffness decreases.